Different contributions of plant diversity and soil properties to the community stability in the arid desert ecosystem - Jiang, La-Mei; Sattar, Kunduz; Lü, Guang-Hui; Hu, Dong; Zhang, Jie; Yang, Xiao-Dong (Frontiers in Plant Science, 2022)
As a one of the focuses of ecological research, understanding the regulation of plant diversity on community stability is helpful to reveal the adaption of plant to environmental changes. However, the relationship between plant diversity and community stability is still controversial due to the scale effect of its influencing factors. In this study, we compared the changes in community stability and different plant diversity(i.e., species, functional and phylogenetic diversities) between three communities (i.e., riparian forest, ecotone community and desert shrubs), and across three spatial scales (i.e.,100 m2, 400 m2 and 2500 m2), and then quantified the contribution of soil properties and plant diversity to community stability by using structural equation model (SEM) in the Ebinur Lake Basin Nature Reserve of the Xinjiang Uygur Autonomous Region in the NW China. The results showed that: (1) community stability differed among three communities (ecotone community > desert shrubs > riparian forest). The stability of three communities all decreased with the increase of spatial scale (2) species diversity, phylogenetic richness and the mean pairwise phylogenetic distance were higher in ecotone community than that in desert shrubs and riparian forest, while the mean nearest taxa distance showed as riparian forest > ecotone community > desert shrubs. (3) Soil ammonium nitrogen and total phosphorus had the significant direct negative and positive effects on the community stability, respectively. Soil ammonium nitrogen and total phosphorus also indirectly affected community stability by adjusting plant diversity. The interaction among species, functional and phylogenetic diversities also regulated the variation of community stability across the spatial scales. Our results suggested that the effect of plant diversities on community stability were greater than that of soil factors. The asynchronous effect caused by the changes in species composition and functional traits among communities had a positive impact on the stability. Our study provided a theoretical support for the conservation and management of biodiversity and community functions in desert areas.